Transition Dilemma in a Closely Held Family Business: A Case of Excel Transporters - Joshi, Manoj; Sinha, Amit K.; Dixit, Shailja; Shukla, Balvinder (European Journal of Family Business, 2018)
The purpose of this case study is to investigate issues that arise at the time of transition of ownership, business and wealth in a multigenerational closely held family business (CHFB). This is particularly relevant if the founder owner-manager has to pass the heir-ship to the offspring and specifically if the incumbent is a women. Through this case, authors have made an attempt to discuss the significance of ownership structure, to plan transition and to mitigate conflicts at the time of generational transition.The case is based on primary research and secondary information, and has been tested several times post, which the gaps were identified and filled. The results indicate that absence of the corporate governance (ownership) structure leads to conflicts during transfer of power position in a CHFB. This reflects the necessity of professionalizing the family business to avoid breakdown of communication and trust within the family unit. Inadequately prepared heirs, forced entries of siblings in the business with no competence besides the patriarchs’ distribution of ownership and business were of major concern in a CHFB.